RECOMMENDATIONS FOR THE SAFETY EVALUATION OF TAILING FACILITIES IN THE CLOSURE STAGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
Scientific and methodological approaches to the development of national regulatory documents for assessing the safety of tailings located in geomorphologically and seismically active mountain areas are outlined. The methodology is based on an expert analysis of the durability of hydro- and geotechnical facilities, structures in accordance with the criteria of international practice, and a probabilistic representation of the formed risks of destruction and consequences.
Keywords: safety; probability; risk assessment; international best practice; tailings; eutrophication, ecological assessment of ecosystems, sustainable development, trophic status, pollution of water bodies.